Organizational Harmony in Hindu Higher Educatiob Institution based on Tri Hita Karana Culture - I Gede Sedana Suci; Ahmad Sonhadji; Ali Imron; Imron Arifin (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
Universities as knowledge-based organizations need to have a conducive, adaptive and flexible structure and culture, in facing any changes. The ideals of becoming a professional organization can be realized, but it demands the organizational components involved directly in the process of forming human resources, ie employees and lecturers must have a harmonious relationship, it should be realized that the harmonization in the college organization is very important. It takes individual awareness, as well as their communal role within the organization to avoid disharmony. Therefore, a good culture is created within the organization. Hinduism teachings taught the concept of Tri Hita Karana or three causes of happiness, in which the achievement of harmonious relationships based of aspects of religious, sociological and ecological. In the implementation these three causes are integrated with each other and mutually influence the creation of harmony of organization goals will be more easily achieved.